DNA recognition element required for PUF-I mediated cell-type-specific transcription of the rat prolactin gene. - Sharp, Z D (1989)
The cell-type-specific transcription of the prolactin gene in vitro is mediated through the interaction of prolactin upstream factor I (PUF-I) with a 28 basepair region of the gene promoter (-63 to -36) which contains an 18 bp A+T-rich imperfect palindrome (-63 to -46). Base substitutions were introduced into 16 of the 18 palindromic residues by targeted saturation mutagenesis. The GH3 binding and in vitro transcription assays of the mutated promoters showed that base substitutions within the 5'-ATATTCA-3' sequence located at -52 to -46 were detrimental to PUF-I binding and its cell-type-specific transcriptional enhancement activity. Transcription assays of the mutated promoters performed with several nonpituitary-derived extracts demonstrated that a distal TATA box located from -59 to -53 promotes initiation at -27. Thus, the cell-type-specific cis-acting element required by PUF-I for DNA recognition is immediately adjacent to a general TATA sequence. Base substitutions that decreased +1 transcription and PUF-I binding concomitantly increased -27 initiation of RNA in vitro. We suggest that PUF-I binding in pituitary cells potentiates +1 transcription and represses alternative TATA box activity for initiation events occurring at -27. This is the first known report of a eukaryotic DNA binding protein that has both an activator and repressor activity for a single transcription unit.